On location : theory and practice in classroom-based writing tutoring - Spigelman, Candace, 1947-; Grobman, Laurie, 1962- (UPCC book collections on Project MUSE., 2005)
Classroom-based writing tutoring is a distinct form of writing support, a hybrid instructional method that engages multiple voices and texts within the college classroom. Tutors work ''on location'' in the thick of writing instruction and writing activity.